Hubungan antara Chronic Kidney Disease (CKD) dengan hipotiroid di RSUP Dr. Kariadi Semarang, Indonesia - I Gede Ardy Surya Dharmanta; Indranila Kustarini Samsuria (Intisari Sains Medis, 2019)
Background: Thyroid hormone in many previous studies have been linked to chronic kidney disease (CKD). There are several interactions between renal dysfunction and thyroid hormones that influence each other. The aim of this study was to see the effect of CKD on the thyroid.Methods: Cross sectional studies on subject data taken retrospectively by looking at medical records on a single center Dr. Kariadi Semarang Hospital during the period 1 June 2017 – 1 June 2018 to then observe the correlation effect of CKD on thyroid hormones by comparing serum urea and creatinine with T3, T4 andTSH.Results: There was a significant correlation of CKD on T3 and TSH levels with ureum (p = 0.020 and p = 0,0,25), and there was a significantly weak correltaion with creatinin (p = 0,081), but there was no significant correlation in T4 (p=0,102; p = 0,108).Conclusion: The results of this study can be concluded that there is a significant correlation between Chronic Kidney Disease (CKD and hypothyroidism, especially the correltation effect of T3 with ureum and creatinine, and TSH with ureum.